WHO SRQ-20 OUTCOMES IN MOTHERS OF CHILDREN 6-23 MONTHS BY FECAL DISPOSAL AND DRINKING WATER SOURCE FACTORS - Muhamad Z. Saefurrohim; Intan Zainafree; Muhammad A. Fitrah; Dewi N.D. Utomo (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Most studies tended to focus on the association of health conditions or tantrum behavior in toddlers with maternal mental health. There was limited in-depth research on the relationship between environmental quality, such as fecal disposal and drinking water sources, and maternal mental health. Objective : This study aimed to determine the differences in WHO SRQ-20 scores and the association of WHO SRQ-20 outcomes with fecal disposal factors and drinking water sources. Research Methods/ Implementation Methods : This study used secondary data from RISKESDAS 2018, involving 670 mothers with children aged 6-23 months. The WHO SRQ-20 questionnaire was used to measure general mental health disorders. Mann-Whitney analysis was conducted to determine the difference in scores, while Chi-Square was used to examine the association of WHO SRQ-20 outcomes with toddler feces disposal factors and drinking water sources. All analyses were performed using SPSS 22.0, with a significance value of <0.05. Results : The analysis showed that inappropriate fecal disposal and poor drinking water sources increased the total WHO SRQ-20 score (p=0.003, & p=0.041). Both factors were positively correlated with seven common mental health symptoms in mothers with children aged 6-23 months, including no appetite, difficulty thinking, difficulty making decisions, feelings of fear, trembling hands, and indigestion, with significant p-values (p<0.05) for each symptom. Conclusion/Lesson Learned : Environmental quality, especially inappropriate fecal disposal and poor drinking water sources, was significantly correlated with increased mental health symptoms among mothers with children aged 6-23 months.